Impact of Product, Process, Organisational, and Marketing Innovation on Micro, Small and Medium Scale Enterprises' Sustainability - Erna Listyaningsih; Yuliansyah Yuliansyah; Rissa A. Martinouva; Febrianty Febrianty; Muazza Muazza; Shofia Amin; Etty Puji Lestari; Amirul Mukminin (Ianna Journal of Interdisciplinary Studies)
Background: Rapid and efficient adoption of new business models is a key lever for improving an organisation's sustainable performance and one of the most important sources of enduring competitive edge. Nonetheless, studies show that a large number of business model innovations fail.